A Trilogia do Armário: a encenação teatral como prática de liberdade no processo de estilização da vida - NUNES, Kauan Amora (Universidade Federal do Pará, 2018)
It is inside of this closet that this research aims to investigate my theatrical stagings, wich i consider my immanence and composition soil. They are as follows: Ao Vosso Ventre (2012), Amem! (2013) and Santa Pocilga de Misericórdia (2014). From the realization of what I call Trilogy of the Closet, having as methodological north the four variations of the attention of the cartographer, I intend to imply an approximation of the theoretical reflection on Self-Care of the discussion about the craft of theater director in the city of Bethlehem to then investigate how my theatrical stagings, already mentioned can be defended as a practice of freedom, a lifestyle, which implies an ethical and aesthetic existence. I follow accompanied by the Nietzsche and Foucault's philosophical thoughts to answer a starter question: Is it possible to think the theatrical staging processes of a gay artist as a practice of freedom committed to a process of stylization of life? I think there is a line that runs through these three staging processes where I can find many similarities and differences that point to a stylization of life. My theatrical stagings transform my process of getting out of the closet in an invitation to problematize the very act of hiding in the closet in first place.